Diskit Khartsan Ltd. in 2013 : hatching a solution - Markovich, Sarit, (SAGE knowledge. Cases., 2016)
Tel Aviv-based Diskit Khartsan Ltd. sold sprays, traps, and netting to combat Blatta lateralis, the Israeli flying cockroach. The insect, slightly over one inch (2.54 cm) long and capable of flying short distances, was noisy, unsightly, and posed a risk of food contamination. Every heat wave brought more infestations, and consumers across the Mediterranean armed themselves with Diskit's HLHT brand products. HLH products generated nearly two-thirds of Diskit's annual revenues. During periods of low demand, local retailers resisted devoting significant shelf space to the bulky products, which meant that during periods of high demand stockouts occurred frequently and Diskit lost sales. This case study discusses this issue.